2010
DOI: 10.1021/ic101221z
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Sulfur Oxygenation of the Ruthenium Dithiolate (4,7-Bis-(2′-methyl-2′-mercaptopropyl)-1-thia-4,7-diazacyclononane)RuPPh3 under Limiting O2 Conditions Yields Thiolato/Sulfinato, Sulfenato/Sulfinato, and Bis-Sulfinato Derivatives

Abstract: The ruthenium(II) dithiolate complex (bmmp-TASN)RuPPh(3) (1) reacts with O(2) under limiting conditions to yield isolable sulfur oxygenated derivatives as a function of reaction time. With this approach, a family of sulfur-oxygenates has been prepared and isolated without the need for O-atom transfer agents or column chromatography. Addition of 5 equiv of O(2) to 1 yields the thiolato/sulfinato complex (bmmp-O(2)-TASN)RuPPh(3) (2) in 70% yield within 5 min. Increasing the reaction time to 12 h yields the sulfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 56 publications
0
32
0
Order By: Relevance
“…However, this is more than offset by the substantial decrease in the enthalpy of activation upon S-oxidation. Notably, the enhanced Lewis acidity of the metal center upon S-oxidation, as noted in electrochemical studies (positive shift of half potential as result of sulfur oxidation) and XAS and DFT studies on L n RuPPh 3 , 19,26 is also expected to lower the enthalpic barrier. The further lowering of the enthalpy of activation of Co-NHase relative to L 2 RuPPh 3 and L 3 RuPPh 3 can be attributed to the greater Lewis of acidity of Co(III) as compared to Ru(II).…”
Section: Inorganic Chemistrymentioning
confidence: 96%
“…However, this is more than offset by the substantial decrease in the enthalpy of activation upon S-oxidation. Notably, the enhanced Lewis acidity of the metal center upon S-oxidation, as noted in electrochemical studies (positive shift of half potential as result of sulfur oxidation) and XAS and DFT studies on L n RuPPh 3 , 19,26 is also expected to lower the enthalpic barrier. The further lowering of the enthalpy of activation of Co-NHase relative to L 2 RuPPh 3 and L 3 RuPPh 3 can be attributed to the greater Lewis of acidity of Co(III) as compared to Ru(II).…”
Section: Inorganic Chemistrymentioning
confidence: 96%
“…1622 However, few of these have even modest nitrile hydrolysis activity, and most of those that utilize oxidized sulfur contain bis-sulfinate ligands since controlling the extent of oxidation of the metal-bound thiolates has proven difficult. 23 This has been especially true for reactions of thiolates with oxygen, as opposed to O-atom transfer reagents, which tend to yield sulfinato complexes. 18, 2334 Nonetheless, oxygen is believed to be the oxidant in vivo for modification of the sulfur atoms of NHase.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies using acetonitrile as substrate showed that complex 48 did not hydrate the nitrile, whereas with both 49 and 50 sub-stoichiometric activity was noticed. 81 These results further inspired detailed studies to determine effect of sulfur-oxidation, temperature, inhibitor, substrate ratio, and metal-centered oxidation state on catalytic activity that are the focus of Chapter 3 in this dissertation. Chapter 4 extends the study to include kinetic assays and Chapter 5 includes DFT studies.…”
Section: Ru-model Complexes From Grapperhaus Labmentioning
confidence: 92%
“…The ligand H2(bmmp-TASN) and precatalysts L 2-3 RuPPh3 were prepared as described in the literature and precatalyst L 1 RuPPh3 was prepared through a slight modification to the procedure reported in literature. 74,[80][81]83 A 0.500 mL aliquot of stock solution of L 1-3 RuPPh3 in benzonitrile (5.4 X 10 -4 M), measured using an automatic micropipette was transferred to 3 mL screw-top vial containing the desired quantities of benzonitrile and water to make a total volume of 2.000 mL. The vial was capped using an air-tight teflon screw cap under argon atmosphere.…”
Section: Materials and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation